(untitled) (LACCEI, 2024)
The present research work focused on the variation of compressive strength generated by the increase in the resistance of mortar with the inclusion of additives. The processes for the elaboration of the test specimens were carried out in accordance with the Peruvian Technical Standards (NTP) as well as the International Standards, (E.070, NTG 41050, ASTM C270-10). Different tests were carried out to obtain as a result the axial resistance of the mortar – brick, after the design of mixing the mortar without additive and the mortars with additive (lime and HT-SikaLatex) with percentages of 4% and 6%, bricks of type II and solid type classified by their resistance and origin (artisanal and industrial) were used to estimate the variation of compressive strength in the piles of masonry units, specimens were tested with mortar without additive and specimens with mortar and lime or HT-SikaLatex, with the proportions of 4% and 6%. To determine this resistance, the physical-mechanical properties of the materials used were previously verified, considering the standard laboratory tests for both the materials, as well as for mortar specimens and brick piles with mortar complying with current regulations. The results show that the compressive strength of the stacks of masonry units tested is directly related to the amount of additive increased for any of the types of brick and additive, being able to generate increases between 1.28% to 6.99% for walls with artisanal brick, and from 1.80% to 3.90% for industrial brick walls, reaching the smallest and highest increase with the additive Cal at 4% and HT-SikaLatex at 6% respectively.